From Past to Present Authentic Leadership and its Reflections on Healthcare Field - Hasan Fehmi Dirik; Şeyda Seren İntepeler (Association of Nurse Managers, 2019)
In today's continuously changing and complex system of healthcare, the role of the leader is discussed as a pivotal factor in providing high quality and safe healthcare for patients as well as in maintaining the wellbeing of healthcare professionals. At the same time, studies continue in search for a multifaceted leadership model that will respond to needs in all processes of healthcare. In this context, it is important in terms of providing guidance to healthcare professionals and administrators that the various dimensions of different leadership approaches are understood fully and that the potential impact of these approaches on the field of healthcare is discussed. In particular, a review of the field literature from 2000 onwards reveals that the prominent styles of contemporary or new generation approaches today are transactional, transformational, servant and authentic leadership. This compilation concentrates on the authentic leadership approach, which can be distinguished from the other new generation leadership styles by its focus on the framework of ethics, self-awareness and the emphasis on transparency in leader-follower relations. The research was inspired by the fact that limited study on authentic leadership in the field of healthcare has been encountered in the national literature. It is hoped that the study will serve healthcare administrators and other professionals as a resource that will enable them to develop leadership skills based on a different approach, forming a basis for further research.